Challenges in activation of remote monitoring in patients with cardiac rhythm devices during the coronavirus (COVID-19) pandemic. (1st April 2021) - Auricchio, Angelo; Conte, Giulio; Demarchi, Andrea; Baldi, Enrico; Özkartal, Tardu; Regoli, Francois; Moccetti, Tiziano
Abstract: Background: Remote monitoring (RM) technology embedded in cardiac rhythm devices permits continuous monitoring of device function, and recording of selected cardiac physiological parameters and cardiac arrhythmias and may be of utmost utility during Coronavirus (COVID-19) pandemic, when in-person office visit for regular follow-up were postponed. However, patients not alredy followed-up via RM represent a challenging group of patients to be managed during the lockdown. Methods: We reviewed patient files scheduled for an outpatient visit between January 1, 2020 and May 11th, 2020 to assess the proportion of patients in whom RM activation was possible without office visit, and compared them to those scheduled for visit before the lockdown. Results: During COVID-19 pandemic, RM activation was feasible in a minority of patients (7.8% of patients) expected at outpatient clinic for a follow-up visit and device check-up. This was possible in a good proportion of complex implantable devices such as cardiac resynchronization therapy and implantable cardioverter defibrillator but only in a minority of patients with a pacemaker the RM function could be activated during the period of restricted access to hospital. Conclusions: Our experience strongly suggest to consider the systematic activation of RM function at the time of implantation or – by default programming - in all cardiac rhythm management devices. Highlights: Remote Monitoring is associated with improved survival patients not followed-up via RM represent a challenging group of patients to be managed, specially during pandemic We strongly suggest to consider the systematic activation of RM function at the time of implantation or – by default programming - in all cardiac rhythm management devices